Nature of Science (NoS) Oriented in Improving Students' Science Process Skills - Ayu Candra Dewi Wesnawati; K. Suma; I W. Subagia (Jurnal Pendidikan dan Pengajaran, 2022)
Science process skills enable students to understand, develop, and discover the nature of science using the scientific method. But in reality the science learning process in Indonesia fails to train students' science process skills. Science learning resources in the form of a NoS-oriented website helps and guides students to learn independently during and after the covid 19 pandemic. The aim of this study is to produce a product in the form of a NoS-oriented science learning resource in the form of a website that is valid, practical, and effective to use. The research subjects were selected using a purposive sampling technique consisting of two material experts, one media expert, one linguist, 15 science teachers, and 40 classes of VIII grade students. This research was designed by modifying the Thiagarajan development model which consists of define, design, and develop stages. The field trial design in this study used a one group pre-posttest design. Data were analyzed using qualitative and quantitative descriptive analysis techniques. The results show NoS-oriented learning stages has a focus on training students' science process skills which is presented in the form of a website. The product of this research is very valid on the material aspect. Based on user assessment, this research product is very practical. NoS-oriented science learning resources in the form of websites have been valid, practical, and effective in improving students' science process skills.